Issues in design and interpretation of MDR-TB clinical trials: report of the first Global MDR-TB Clinical Trials Landscape Meeting. Issue 8 (December 2015) - Mitnick, Carole; Rusen, ID; Bain, Lisa; Horsburgh, C
Abstract Recognizing that the current MDR-TB regimen is suboptimal and based on low-quality evidence, the Global MDR-TB Clinical Trials Landscape Meeting was held in December, 2014 to strategize about coordination of research and development of new treatment regimens for this disease that affects millions of people worldwide every year. Sixty international experts on multidrug-resistant tuberculosis (MDR-TB) met in Washington D.C. and Cape Town, South Africa to consider key MDR-TB trial-related issues, including: standardization of definitions; clinical trial capacity building and; regimens optimized to foster compliance, avoid the emergence of resistance and have clinical relevance for special populations, including children and those co-infected with HIV. Underpinning all of this is the generation of a sufficient evidence base to facilitate regulatory approval and improved normative guidance. Participants discussed treatment combinations currently being studied in Phase 2B and Phase 3 trials as well as other promising new regimens and combinations that may be evaluated in the near future. These include regimens designed specifically to enable shorter duration and all-oral treatment as a means of maximizing treatment completion. It is hoped that clear definition of these challenges will facilitate the process of identifying solutions that accelerate progress towards effective, non-toxic treatments that can be programmatically implemented.